2019
DOI: 10.1063/1.5096429
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-liquid separation of aqueous solutions: A molecular dynamics study

Abstract: In the liquid-liquid phase transition scenario, supercooled water separates into the high density liquid (HDL) and low density liquid (LDL) phases at temperatures lower than the second critical point. We investigate the effects of hydrophilic and hydrophobic solutes on the liquid-liquid phase transition using molecular dynamics simulations. It is found that a supercooled aqueous NaCl solution separates into solute-rich HDL and solute-poor LDL parts at low pressures. By contrast, a supercooled aqueous Ne soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 103 publications
0
13
1
Order By: Relevance
“…However, the slow rate (i.e. O(10 3 sec)) by which these events are occurring is inconsistent with expectations from an LLPS molecular dynamics (MD) simulation published recently (Yagasaki et al, 2019). Therefore, the slow non-correlated exchange rate, the association of bursts with exchange events of slncRNA-CP complexes (rather than just CPs), and the filament-like structure appearing in the in vitro images suggest that the synthetic RNP granules seem to exhibit gel or glass-like properties, rather than classic liquid or solid-like characteristics.…”
Section: Resultscontrasting
confidence: 72%
“…However, the slow rate (i.e. O(10 3 sec)) by which these events are occurring is inconsistent with expectations from an LLPS molecular dynamics (MD) simulation published recently (Yagasaki et al, 2019). Therefore, the slow non-correlated exchange rate, the association of bursts with exchange events of slncRNA-CP complexes (rather than just CPs), and the filament-like structure appearing in the in vitro images suggest that the synthetic RNP granules seem to exhibit gel or glass-like properties, rather than classic liquid or solid-like characteristics.…”
Section: Resultscontrasting
confidence: 72%
“…When the LDS was compressed at the same temperature, the volume started to decrease rapidly at ∼0.14 GPa, and then, the LDS transformed to the original HDS. In the case of the polyamorphic transition of the aqueous solution, it is suggested that low-density and high-density states coexist in a pressure region between the beginning and end of the polyamorphic transition ( 14 , 37 , 38 ). Now, the HDS-to-LDS transition pressure, P HtoL , and the LDS-to-HDS transition pressure, P LtoH , are defined as the middle pressure between onset and offset transition pressures for each polyamorphic transition.…”
Section: Resultsmentioning
confidence: 99%
“…14 The temperature of a liquid-liquid phase transition in aqueous NaCl solutions is predicted by molecular dynamics studies to be higher than that for pure water. 50,51 We do not observe any change in the OD stretching mode indicating a change to a more tetrahedral water structure which would be definitive evidence of a water liquidliquid transition.…”
Section: Discussionmentioning
confidence: 58%